A Radical Access to Highly Functionalized Tetrahydroxanthones. Issue 33 (4th July 2013) - Meister, Anne C.; Nieger, Martin; Bräse, Stefan
<x xml:space="preserve">Abstract</x> Center stage: A radical synthesis of highly functionalized tetrahydroxanthones is presented. The key step, the build‐up of the quarternary stereocenter, is performed through a diastereoselective intramolecular radical Michael addition (see scheme). This offers versatile access to three different precursors for natural products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>